Marketing the Community-Based Eco-tourism for Thai and Chinese under the New Media Era for Local Authorities - YANG, Wei; BI, Chuanchen (Journal of Ecohumanism, 2024)
Based on a research of a Thailand's Best Responsible Tourism award-winner in Sapphaya Community in Chai Nat Province, this study uncovered the critical sustainability drivers for effective social marketing or Community-Based Eco-tourism (CBTEs). One way to protect the environment and boost the local economy is through ecotourism. It does, however, overlook the local community, which is a crucial component of sustainable development. A type of ecotourism known as community-based ecotourism (CBET) places greater emphasis on the advantages for, and ability to participate in, local communities. Community-Based Tourism (CBT), which represents more positive trends than those linked to more traditional forms of tourism in Thailand, has grown significantly in the last ten years thanks to the efforts of researchers, environmental activists, non-governmental organisations, and public officials. Even though certain rural communities in Thailand have difficulty organising, starting, and maintaining CBT programs, successful CBT may still be pursued under the correct conditions. The study also looks at how the CBTE might improve local cooperation amongst several stakeholders. According to our research, leadership and local involvement are two important sustainability drivers for sustainable social companies. It is suggested to use an emerging leadership and community involvement strategy to promote the sustainability of CBTEs. It suggests that CBTE leadership is important and plays a crucial role in developing social capital and preserving community endowments, such as historical places and cultural treasures. The main driver of sustainable tourism is local involvement with a strong feeling of ownership and community participation. The findings also point to potential policy implications and practical procedures for growing sustainable social companies.